EFFICACY OF MYCOPHENOLATE MOFETIL VERSUS CYCLOPHOSPHAMIDE IN THE TREATMENT OF LUPUS NEPHRITIS - MANTADA, PRASANTHA KUMARI; PRIYANKA, MATHEPRASANNA; BHARGAVI, LINGATHOTI; BABU, PAIDIPOGU LAKSHMAN; RASAGNA, YALAVARTHI SAI; MALAMANTI, SAI KRISHNA; JYOTHSNA, SANKURI (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objective: Despite the prevalence of SLE, lupus nephritis (LN) is the primary cause of morbidity and mortality. This study objective was to assess the efficacy and safety of the induction treatment with mycophenolate mofetil (MMF) and cyclophosphamide (CYC). Methods: This was a prospective observational study enrolled 100 LN patients who were treated with MMF and cyclophosphamide. In this study, 6 male and 44 female patients were treated with MMF and 3 male and 47 female patients were treated with cyclophosphamide. To estimate drug efficacy, patients were evaluated for 24-h urinary protein excretion estimation, serum creatinine, protein-creatinine ratio (PCR), Proteinuria, Serum complement C3, Serum complement C4, and Serum albumin. The primary end point was a prespecified decrease in urine PCR and stabilization of serum creatinine. Secondary end points were complete renal remission, systemic disease status and safety. Results: The results indicated a potential small advantage of MMF over CYC although the results were not significant. Serum creatinine, 24-h urine protein, and serum albumin were also similar between the MMF and CYC groups after induction therapy. Leukopenia was significantly reduced in MMF treated patients. Both groups suffered from upper gastrointestinal symptoms, but the MMF group’s symptoms were mild and self-limited. MMF therapy was effective in reducing proteinuria and boosting serum complement levels. Conclusion: MMF and CYC were not significantly different in remission induction therapies for LN. Clinical improvement was seen in most patients in both treatment groups.